The Manipulation of History and Memory in Contemporary American Poetry: A Study of Ekphrasis in the Poetry of Jorie Graham - Jabbar, Amjed L. (Al-Adab Journal, 2015)
Ekphrasis enables poets to invade the most difficult and sensitive areas of thought without the pressure of direct expression. Ekphrastic poetry has a tendency to draw together contradictions; the work of art acting as intermediary between points of opposition, tension and contrast. The presence of the ekphrastic object in a poem is an acknowledgement of the unbridgeable hermeneutic gap between poetry, history and the real, indeed it often acts as the marker that exposes this gap. Also in a practical way, through both its critical and art-historical backgrounds, the practice of ekphrasis is located very firmly within arguments of a temporal nature; it is important to remember that paintings have a material history as well as a conceptual one, and that contemporary poetry is increasingly taking into account, and even seeking to replicate in some cases, the space of the museum itself as well as the paintings within it. Therefore, the present paper aims at affording a new study of the poetry of the contemporary American poetess Jorie Graham through illuminating the rhetorical device of ekphrasis, which is meant to verbally represent what is already represented visually, and its relation to presentations of the most perplexing concepts in modern and contemporary literature in general and poetry in particular, namely, memory and personal history. The paper is an attempt to investigate how Jorie Graham uses images from painting, photography and films in her poems to manipulate time and represent personal history through memory which, in turn, leads to a consideration of how she uses ekphrasis to approach the ethics of representing public history, and how she uses the different temporal conventions of each genre to write about the past